The Saccharomyces cerevisiae suppressor of choline sensitivity (SCS2) gene is a multicopy Suppressor of mec1 telomeric silencing defects. - Craven, R J (2001)
Mec1p is a cell cycle checkpoint protein related to the ATM protein kinase family. Certain mec1 mutations or overexpression of Mec1p lead to shortened telomeres and loss of telomeric silencing. We conducted a multicopy suppressor screen for genes that suppress the loss of silencing in strains overexpressing Mec1p. We identified SCS2 (suppressor of choline sensitivity), a gene previously isolated as a suppressor of defects in inositol synthesis. Deletion of SCS2 resulted in decreased telomeric silencing, and the scs2 mutation increased the rate of cellular senescence observed for mec1-21 tel1 double mutant cells. Genetic analysis revealed that Scs2p probably acts through a different telomeric silencing pathway from that affected by Mec1p.